2017
DOI: 10.1016/j.toxicon.2017.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution takes the sting out of it: Evolutionary biology and mechanisms of toxin resistance in animals

Abstract: Understanding how biotic interactions shape the genomes of the interacting species is a long-sought goal of evolutionary biology that has been hampered by the scarcity of tractable systems in which specific genomic features can be linked to complex phenotypes involved in interspecific interactions. In this review we present the compelling case of evolved resistance to the toxic challenge of venomous or poisonous animals as one such system. Animal venoms and poisons can be comprised of few or of many individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 173 publications
(219 reference statements)
3
67
0
4
Order By: Relevance
“…; Arbuckle et al . ). However, whether these cases are taxon specific or form the general rule across all venomous snakes has yet to be tested at a broad taxonomic scale.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Arbuckle et al . ). However, whether these cases are taxon specific or form the general rule across all venomous snakes has yet to be tested at a broad taxonomic scale.…”
Section: Introductionmentioning
confidence: 97%
“…Species are highlighted as silhouettes with colours matching the incapacitation ability scale from (a). (Daltry et al 1996;da Silva & Aird 2001;Mackessy et al 2006;Starkov et al 2007;Barlow et al 2009;Richards et al 2012;Vonk et al 2013;Margres et al 2017), while other examples have either found no such prey-specificity (Williams et al 1988) or cases were the prey species have evolved tolerance towards their predator's venoms (Heatwole & Poran 1995;Biardi et al 2000;Voss 2013;Pomento et al 2016;Arbuckle et al 2017). However, whether these cases are taxon specific or form the general rule across all venomous snakes has yet to be tested at a broad taxonomic scale.…”
Section: Introductionmentioning
confidence: 99%
“…This again suggests a predominant role of diet in driving venom evolution since there is no obvious reason that, for instance, predation risk should typically change greatly following a shift of diet (as would be necessary for inferring a primarily defensive role). However, as striking and informative as these relationships are, coevolution can lead to defensive toxin resistance to snake venom in prey species [24,25], obscuring clear positive relationships between toxicity and natural diet. Moreover, given that the ultimate function of a predatory snake venom is to incapacitate rather than kill prey [26], which may not be mechanistically identical processes, the standard use of lethality as a measure of toxicity blurs the interpretation of such data from an evolutionary ecological perspective to some degree.…”
Section: Introductionmentioning
confidence: 99%
“…Coevolutionary arms races are often invoked to account for diversity in venom composition and activity, as well as the dynamic molecular evolution of toxin genes (e.g., Casewell et al, 2013). On the other hand, interest in the evolution of resistance to venom in both the prey and predators of venomous organisms has also increased recently (after a long history of piecemeal research), highlighted by the publication of two excellent reviews (Holding et al, 2016 andArbuckle et al, 2017) detailing the multiple molecular innovations that confer this resistance. The evolution of chemical weaponry and the reciprocal evolution of resistance may be one of the most important drivers of functional diversity at the molecular level.…”
Section: Antagonistic Coevolutionmentioning
confidence: 99%